Prescribing patterns and pharmacoeconomic analysis of antihypertensive drugs in South Indian population: A cross-sectional study - S Shanmugapriya; Saravanan Thangavelu; Aashiq Ahamed Shukkoor; P Janani; R Monisha; Varsha Elsa Scaria (Perspectives in Clinical Research, 2023)
Background: Global evidence-based recommendations for hypertension management are periodically updated, and ensuring adherence to the guidelines is imperative. Furthermore, the current high prevalence of hypertension effectuates a high health-care cost. Purpose: To evaluate the prescribing patterns of antihypertensive drugs and other factors affecting blood pressure (BP) with the objective of assessing the proportion of patients achieving the target BP and to perform a pharmacoeconomic analysis in a South Indian population. Materials and Methods: In a cross-sectional study, 650 patients previously diagnosed with hypertension and already on treatment with one or more drugs were included. A prospective interview of patients was done using a prevalidated questionnaire on various factors in BP control. Prescribing patterns and pharmacoeconomic analyses, namely, cost acquisition, cost of illness, and cost-effectiveness analyses were carried out. Results: Of 650 subjects, 257 (39.54%) achieved the target BP, while 393 (60.46%) did not. A significant association of age, occupational status, monthly family income, and area of residence in addition to physical activity and diet scores, with achieving target BP was noted. A significantly higher cost of anti-hypertensive drug treatment in achieving target BP (P = 0.02) was observed. Among patients who achieved target BP, 37.35% were on monotherapy and 48.25% on multiple drug therapy compared to 46.31% and 35.62%, respectively, in patients who did not. Average cost-effectiveness ratio were found to be Rs. 20.45 and Rs. 57.27, respectively, for single and multiple drug therapies, with incremental cost-effectiveness of Rs. 194.14 per additional patient treated with multiple free drug combinations. Conclusion: This study identified the anti-hypertensive prescribing pattern and provided insight into the various pharmacoeconomic factors that play a significant role in attaining target BP in the treated population.